Death, Burial and Commemoration in Ireland, 1550-1650 - Tait, C. author. aut Link
XI, 229 p.
Keywords: This book is the first detailed examination of death in early modern Ireland. It deals with the process of dying, the conduct of funerals, the arrangement of burials, the private and public commemoration of the dead, and ideas about the afterlife. It further considers ways in which the living fashioned ceremonies of death and the reputations of the dead to support their own ends. It will be of interest to those concerned with Irish history and death studies generally.